2021
DOI: 10.1016/j.ajog.2021.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy alters interleukin-1 beta expression and antiviral antibody responses during severe acute respiratory syndrome coronavirus 2 infection

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the disease-causing pathogen of the COVID-19 pandemic, has resulted in morbidity and mortality worldwide. Pregnant women are more susceptible to severe COVID-19 disease and are at higher risk for preterm birth compared to uninfected pregnant women. Despite this evidence, the immunological effects of SARS-CoV-2 infection during pregnancy remain understudied. Objective To assess the impact of SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
1
32
1
1
Order By: Relevance
“…Indeed, neonates with raised IP-10 concentrations were born to mothers who had high plasma IP-10 measurements, although in general concentrations were significantly lower in neonates compared to mothers. However, in the case of cord plasma CXCL8, a chemokine that correlated strongly with maternal IL-1β (previously associated with maternal SARS-CoV-2 infection 35 ), levels were significantly higher than those observed in their mothers, suggesting that at least some of these elevated cytokines were neonatally derived, and a direct response to maternal infection. Elevated cord plasma cytokines, including CXCL8, have been previously observed in some neonates born to SARS-CoV-2-positive mothers 17 .…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, neonates with raised IP-10 concentrations were born to mothers who had high plasma IP-10 measurements, although in general concentrations were significantly lower in neonates compared to mothers. However, in the case of cord plasma CXCL8, a chemokine that correlated strongly with maternal IL-1β (previously associated with maternal SARS-CoV-2 infection 35 ), levels were significantly higher than those observed in their mothers, suggesting that at least some of these elevated cytokines were neonatally derived, and a direct response to maternal infection. Elevated cord plasma cytokines, including CXCL8, have been previously observed in some neonates born to SARS-CoV-2-positive mothers 17 .…”
Section: Discussionmentioning
confidence: 70%
“…The sensitivity analysis excluding participants in active labor showed similar results for cluster Eigenvalues compared between cases and controls (Supplementary table IX). CoV-2 infected pregnant people (n=33) and non-infected pregnant people (n=17) based on RT-PCR testing and did not find altered gene expression levels of IL-1β and IL-6 [18]. However, they did find increased levels of IL-1β in maternal blood taken within 14 days of infection compared to samples taken 14 days after infection [18].…”
Section: Association Between Anti-s Igg Status and Cluster Eigenvaluesmentioning
confidence: 89%
“…CoV-2 infected pregnant people (n=33) and non-infected pregnant people (n=17) based on RT-PCR testing and did not find altered gene expression levels of IL-1β and IL-6 [18]. However, they did find increased levels of IL-1β in maternal blood taken within 14 days of infection compared to samples taken 14 days after infection [18]. RT-PCR testing is commonly used to detect viral RNA of SARS-CoV-2 in respiratory secretions and a positive test is often considered an indicator of active viremia, although this is not guaranteed [39].…”
Section: Association Between Anti-s Igg Status and Cluster Eigenvaluesmentioning
confidence: 94%
See 1 more Smart Citation
“…In the context of COVID-19 pandemic and the elevated risk of serious outcomes in pregnancy [ 42 ], it is crucial for pregnant women to be adequately protected against viral infection. Interestingly, data available suggest that antibodies induced by natural SARS-CoV-2 infection during pregnancy may not confer the same neutralizing potential [ 43 ] and be less efficiently transferred to the fetus compared to those generated by vaccination [ 44 ]. In the current study, we reported placental transfer of SARS-CoV-2-specific IgG to the fetuses at ∼15% of the levels seen in the dams.…”
Section: Discussionmentioning
confidence: 99%